The Effectiveness of Wordwall on Fourth-Grade Students’ Learning Outcomes in Fractional Materials at SDN 70 Singkawang - Febrianti, Maria Dona Elsinta; Sunarsih, Eti; Wirawan, Gunta (Jurnal Gentala Pendidikan Dasar, 2025)
This research is a type of pre-experimental research that involves one class as an experimental class. The main objective is to evaluate the effectiveness of the use of Wordwall media on learning outcomes in fractional materials. The effectiveness studied includes three aspects, namely Mathematics learning outcomes, Student Response to the learning process, and Learning Implementation. The subject of this study is fourth grade students of SDN 70 Singkawang consisting of 29 students. The design used in this study is One Group Pretest-Posttest Design, which involves only one group without a control class. Based on the results of the data obtained, only 31.03% of students achieved the level of completeness in Mathematics subjects. Therefore, the use of Wordwall media is needed as a solution to overcome these problems. The results of this study show that 1) The learning outcomes before using Wordwall media were 9 people or 31.03% who achieved minimum completeness, and after using Wordwall media there were 26 people or 89.66% of students who achieved Minimum Completeness, so that based on the results of data processing there was a significant difference between student learning outcomes before and after using Wordwall media. 2) Students’ response to the use of Wordwall media in mathematics learning showed very positive results, which was 96.6%. 3) The implementation of the learning process using Wordwall media is in the very good category.